Tradição popular na literatura infantil e juvenil: leituras do Bumba-meu-boi maranhense - Chagas, Mirian Santos (2016)
This dissertation aims to map, describe and interpretate how Bumba-meu-boi, a manifestation of popular culture, is configured in Children and Young Adult Literature. Concerning to mapping, the research found in Brazilian editorial market fifteen Children and Young Adult Literature books about Bumba-meu-boi as main theme. When describing the group of books, it was clearly perceived that it could be divided in two subgroups: one subgroup formed by books intended to preserve the traditional auto and one subgroup formed by books that choose to update the auto, both aiming the maintenance and the dissemination of Bumba-meu-boi. In the third throughput of the research, the aesthetic and literary interpretations of the books have been made, aiming to observe the way literature for children and young adult configures literarily this party from popular tradition. For this purpose, Stela Barbieri’s Bumba-meu-boi (2014) has been analyzed at great lenght as an exemple of the group of conservation of tradition; and Carmen Lúcia Campos’ A festa do boi (2007) has been analysed at great lenght as representantive of the dimension of the updating. The selection of these books takes into account that both of them have the Bumba-meu-boi matraca’s ox from State of Maranhão as a reference, also known as accent of the lowlands and of the island. The issues that encircle the confluence between Children and Young Adult Literature and popular tradition dialogue with the studies conducted by Peter Burke, Teresa Colomer, Peter Hunt, and Regina Zilberman. The thinking about Bumba-meu-boi is due, mostly, to the work of Luís da Câmara Cascudo, Mário de Andrade, Maria Laura Cavalcanti, Américo Azevedo, José Ribamar Sousa dos Reis, Luciana Gonçalves de Carvalho, amongst others. The corpus analysis, taking into account the aesthetic assembly formed by illustration and text, has been based on researches conducted by Walter Benjamin, Paul Zumthor, Néstor Garcia Canclini, Maria José Gordo Palo, Maria Rosa Duarte de Oliveira, and Sophie Van Der Linder . The main result of this research is the awareness of that both throughputs (auto’s conservation and updating) that pervade the representation of Bumba-meu-boi in Children and Young Adult Literature are complementary and brought together to preserve and disseminate tradition, mantaining the link between new generation and ancestry through Children and Young Adult Literature